Experimental Research on Reconstruction Techniques for Instantaneous Regression Rate of Hybrid Rocket Motor with Single-Port Wagon Wheel Fuel Grain - Tianfang Wei; Guobiao Cai; Hui Tian; Yuanjun Zhang; Chengen Li; Xiangyu Meng (Aerospace, 2023)
This study investigated reconstruction techniques for building the instantaneous fuel regression rate of the hybrid rocket motor (HRM). Specifically, an experiment in a laboratory 500 N-class hybrid rocket motor with single-port wagon wheel fuel grain, operated with hydrogen peroxide (HP) and hydroxyl-terminated polybutadiene (HTPB) based fuel (including Al), was carried out. A piece of post-processing software was developed to reconstruct the instantaneous regression rate and other performance parameters of the HRM during the firing test. The results produced by the reconstruction techniques are in good agreement with experimental data obtained by traditional methods, with a maximum error of less than 5.75%. Moreover, compared with the traditional endpoint method, the reconstruction method had a significant advantage, which could ascertain the sensitivity of the regression rate to changes in the oxidizer mass flux and fit the formula of regression rate in a single firing test. Additionally, digital image processing techniques were employed to determine the axial distribution of the fuel regression rate after the test using computed tomography (CT) scanning. This served to verify the accuracy of the instantaneous reconstruction calculation. The error in the average regression rate between CT scanning and the reconstruction calculation was 1.91%, proving that the CT scanning and pixel statistic method of the calculating regression rate was practical for characterizing the axial distribution of the average regression rate during the firing test. In summary, the main objective of this study was to reconstruct the transient parameters of hybrid rocket motor with single-port wagon wheel fuel grain using reconstruction techniques, and to fit the formula of the regression rate through a single-firing test. Furthermore, this paper proposes a modified reconstruction method that is essential for investigating fuel regression rate during the firing test of HRMs.